Penggunaan Permainan “Ular Tangga Anak Sehat” Sebagai Media Pembelajaran Untuk Meningkatkan Pengetahuan Cuci Tangan Pakai Sabun Siswa SD Negeri Di Kutoarjo Purworejo - Nur Hidayati; Sigid Sudaryanto; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Washing hand practice by soap (WHS) is needed to be implemented since early age as a pre-ventive effort to the spreading of environment based diseases. One of the main target groups of WHS practice is elementary school students. Elucidation will reach its maximum results when the learning methos and media used are appropriate with the target. For elementary school stu-dents, using games is one of the most appropriate methods and useful for facilitating them in receiving the health messages. “Healthy Kid Snake and Ladder” is one of the games that can be applied. To fulfill the objective of the study. i.e. to know the influence of using the game as learn-ing media for up-levelling the knowledge of WHS among elementary school students in Kutoarjo, Purworejo, a quasi experiment employing pre-test post-test with control group design was con-ducted. The study was held at State Elementary School of Suren as the treatment group, and State Elementary School of Blimbing as the control group. The respondents for each school were 30 students of 4th and 5th grades which were randomly selected. The study data which were analyzed by Mann Whitney test at significancy level (?) 0,05; showed result that the WHS know-ledge in the treatment group were increase significantly compared with those in the control group (p value < 0,001). Therefore, it can be concluded that the game affecting the knowledge of the students on washing hand with soap.